2008
DOI: 10.1097/jcp.0b013e31818b2091
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Peripheral and Central Effects of Single and Repeated Oral Dose Administrations of Bilastine, a New H1 Antihistamine

Abstract: Peripheral anti-H1 and central nervous system (CNS) activities after single (day 1) and repeated (day 7) administrations of increasing doses of bilastine (BIL) were assessed in 20 healthy volunteers throughout a crossover, randomized, double-blind, placebo (PLA)-controlled study. Repeated doses of BIL 20, 40, or 80 mg and hydroxyzine 25 mg (HYD) as positive standard were administered on 7 consecutive days. Before and at several time points after drug intake, skin reactivity to the intradermal injection of hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 37 publications
3
50
0
1
Order By: Relevance
“…Colors of circles for desloratadine are as follows: 5 mg, pale green, 10 mg, mid green, and 20 mg, dark green (total, 38 patients). second-generation antihistamines after 4 to 5 days of administration has been reported repeatedly, [28][29][30] and the weekly stepwise increase in dosage in this study would be ideal to induce tolerance.…”
Section: Discussionmentioning
confidence: 91%
“…Colors of circles for desloratadine are as follows: 5 mg, pale green, 10 mg, mid green, and 20 mg, dark green (total, 38 patients). second-generation antihistamines after 4 to 5 days of administration has been reported repeatedly, [28][29][30] and the weekly stepwise increase in dosage in this study would be ideal to induce tolerance.…”
Section: Discussionmentioning
confidence: 91%
“…In clinical studies, bilastine has been shown to have a rapid onset of action and a long duration of effect [10,11]. Furthermore, bilastine has been shown to be free of cardiotoxicity [12] and sedative effects within the CNS and not to enhance the effects of lorazepam [13], the latter property supported by the observation that bilastine is a substrate for P-glycoprotein, an organic anion transporting protein (OATP) that prevents its uptake across the bloodbrain barrier into the brain [14].…”
Section: Introductionmentioning
confidence: 99%
“…Non-sedating antihistamines do not generally have the effect, although this has been reported by few patients [23, 24]. A double-blinded, placebo-controlled study assessed the influence of bilastine 20, 40, and 80 mg and the sedating anti-histamine hydroxyzine hydrochloride 25 mg on psychomotor functions, when the drugs were taken by healthy subjects with standardized alcohol consumption [25]. Psychomotor functions were measured with objective tests and subjective assessment.…”
Section: Resultsmentioning
confidence: 99%